2014
DOI: 10.5694/mja13.11318
|View full text |Cite|
|
Sign up to set email alerts
|

Firearms, mental illness, dementia and the clinician

Abstract: Summary Clinicians have an obligation to report to state or territory police any concerns about risk of harm from patients with access to firearms. Dementia is an under‐recognised medical problem which may increase the risk of firearm injury or violence in those with such access. There are no guidelines for clinicians regarding mandatory screening for access to firearms, and currently the onus is on the firearm licence holder to declare any relevant medical conditions. We propose that clinicians should screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…This finding suggests a significant gap in practice that may be associated with health care professional uncertainty or concerns about alienating patients, although prior work suggests that patients are open to respectful firearm safety counseling in appropriate contexts. Health care professional training, materials, and resources may facilitate more routine firearm safety counseling for persons with dementia and their families. When asked where they would turn for answers to firearm safety questions, caregivers identified health care professionals as an important source: 10% said they had already looked to them for help, and 53% said they would in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding suggests a significant gap in practice that may be associated with health care professional uncertainty or concerns about alienating patients, although prior work suggests that patients are open to respectful firearm safety counseling in appropriate contexts. Health care professional training, materials, and resources may facilitate more routine firearm safety counseling for persons with dementia and their families. When asked where they would turn for answers to firearm safety questions, caregivers identified health care professionals as an important source: 10% said they had already looked to them for help, and 53% said they would in the future.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests a significant gap in practice that may be associated with health care professional uncertainty or concerns about alienating patients, although prior work16 suggests that patients are open to respectful firearm safety counseling in appropriate contexts. Health care professional training, materials, and resources[16][17][18] may facilitate more routine firearm safety counseling for persons with dementia and their families. When asked where they would turn for answers to firearm safety questions, caregivers identified health care professionals as an important source: 10% said they had already looked to them for help, and 53% said they would in the future.Official policies or guidance by health care organizations, such as the Veterans Health Administration,17 as well as templates to prompt and document counseling 19 may encourage and support health care professionals.In this sample, caregivers reported that many persons with dementia who owned firearms had no plan for what to do with the guns if their illness made it unsafe to handle them.…”
mentioning
confidence: 99%
“…In reply : There was a transcription error in our article 1 . The rate of licensed firearm ownership in Australia in 2001 was indeed 3.9 per 100 people, 2 although this is likely to be an underestimate, as unregistered, unlicensed and illegal firearms are not captured by official statistics.…”
mentioning
confidence: 90%
“…We acknowledged the ethical implications of doctors having a role in assessing suitability for firearm licences 1 . However, there is already an expectation that doctors should notify police when concerns about risk to the community or individuals arise from a patient's access to firearms 3 .…”
mentioning
confidence: 99%
“…To the Editor : In their recent article in the Journal, Wand and colleagues suggest that the medical profession should play a more active role in the regulation of firearm licences held by older Australians 1 . However, the authors underestimate the rate of firearm ownership in Australia by a factor of 1000 when they state that 3.9 per 100 000 people held a firearm license in 2001.…”
mentioning
confidence: 99%